2017
DOI: 10.1021/acs.inorgchem.7b01889
|View full text |Cite
|
Sign up to set email alerts
|

Facile Substitution of Bridging SO22– Ligands in Re12 Bioctahedral Cluster Complexes

Abstract: Selective substitution of μ-SO groups by either O or Se ions occurs upon heating the bioctahedral rhenium cluster complex K[ReCS(μ-SO)(CN)] in air atmosphere or in the presence of a Se source, respectively, manifesting the remarkable lability of SO ligands bound to a transition-metal cluster. A series of compounds based on the new mixed-ligand anions, [ReCS(μ-O)(CN)], [ReCS(μ-Se)(CN)], and [ReCS(μ-O)(OH)], were isolated and their solid-state structures were elucidated by single-crystal X-ray diffraction analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Similar to [{Re 4 (AsO) 3 S}­(CN) 12 ] 7– , the metal cluster “expands” from the average Re–Re distance of 2.78(1) Å in the unoxidized cluster to 2.89(3) Å in the oxidized one. The Re–As and Re–Se bond lengths are in the ranges of 2.4313(16)–2.4716(16) and 2.4747(13)–2.4939(14) Å, respectively, and are in good agreement with the data for the complexes [{Re 4 Se 4 }­(CN) 12 ] 4– ,,, and [{Re 4 (AsO) 4 }­(CN) 12 ]. …”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similar to [{Re 4 (AsO) 3 S}­(CN) 12 ] 7– , the metal cluster “expands” from the average Re–Re distance of 2.78(1) Å in the unoxidized cluster to 2.89(3) Å in the oxidized one. The Re–As and Re–Se bond lengths are in the ranges of 2.4313(16)–2.4716(16) and 2.4747(13)–2.4939(14) Å, respectively, and are in good agreement with the data for the complexes [{Re 4 Se 4 }­(CN) 12 ] 4– ,,, and [{Re 4 (AsO) 4 }­(CN) 12 ]. …”
Section: Resultssupporting
confidence: 79%
“…The Re–Te bonds [2.6424(6)–2.6504(6) Å] practically do not change upon the oxidation of the compound with the {Re 4 (AsO) 2.25 As 0.75 Te} 5+ core, where these distances are in the range from 2.6464(5) to 2.6534(5) Å. The Re–As and As–O bond lengths are 2.4286(9)–2.4529(9) and 1.655(6)–1.669(6) Å, respectively, and are in good agreement with the values observed in both [{Re 4 (AsO) 3 Q}­(CN) 12 ] 7– (Q = S, Se) and [{Re 4 (AsO) 4 }­(CN) 12 ]. The bond lengths for complexes 1–3 are summarized in Table . One can see that the cluster core slightly expands in the row of Q = S–Se–Te, which is associated with an increase in the ionic radius of the chalcogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SO 2 2– ligands are relatively labile and peripheral modifications are possible with retention of the central carbide moiety. Thus, reaction with KSeCN results in selenide-bridged K 6 [Re 12 (μ 6 -C)­(μ-Se) 3 (μ 3 -S) 14 (CN) 6 ], while reaction with O 2 and KOH results in substitution of both the cyanide and SO 2 2– ligands, yielding the oxide-hydroxide complex, K 6 [Re 12 (μ 6 -C)­(μ-O) 3 (μ 3 -S) 14 (OH) 6 ] . Reaction of the oxide-hydroxide complex with HCl or HBr proceeds with two-electron reduction of the cluster, affording (Et 4 N) 5 [Re 12 (μ 6 -C)­(μ-Cl) 3 (μ 3 -S) 14 Cl 6 ] or (Et 4 N) 5 [Re 12 (μ 6 -C)­(μ-Br) 3 (μ 3 -S) 14 Br 6 ] …”
Section: Strategies Toward Bridging Carbide Complexesmentioning
confidence: 99%
“…Thus, reaction with KSeCN results in selenide-bridged K 6 [Re 12 (μ 6 -C)(μ-Se) 3 (μ 3 -S) 14 (CN) 6 ], while reaction with O 2 and KOH results in substitution of both the cyanide and SO 2 2− ligands, yielding the oxide-hydroxide complex, K 6 [Re 12 (μ 6 -C)(μ-O) 3 (μ 3 -S) 14 (OH) 6 ]. 202 Reaction of the oxide-hydroxide complex with HCl or HBr proceeds with two-electron reduction of the cluster, affording 203 Triple bond metathesis between the homoleptic {WW} complex, [( t BuO) 3 WW(O t Bu) 3 ], and alkynes or acetylides readily leads to carbyne or carbide complexes (Figure 36). By contrast, Wolczanski found that the heteroleptic {WW} complex, [( t Bu 3 SiO) 2 ClWWCl(OSi t Bu 3 ) 2 ] reacts with CO and CNAr (Ar = 2,6-Me 2 C 6 H 3 ) to form the 1:2 and 1:…”
Section: Synthesis Of Bridging Carbide Complexes Upon Cn Bond Splittingmentioning
confidence: 99%